The Influence of Perceived Quality on Product Purchase Intention Through Event - Felicia Hanslim; Henri Putra Jaya; Yuliana Riana Prasetyawati (Communicare : Journal of Communication Studies, 2020)
An important consideration factor for consumers to choose home appliances products is product quality. Marketing communication can be a medium for companies to convey information about products and their advantages as well as a stimulus that drives consumers to make purchases. Modena chooses event marketing communication tactics namely Culinaria Modena so consumers can know and experience first hand the quality and features of the product. The purpose of this study was to determine the effect of perceived quality on buying interest through the Culinaria Modena event. The results of the study stated that there is a strong influence between perceived quality on buying interest through events. This states that the event is a strategic marketing communication to build buying interest. It is recommended to Modena to increase the frequency of organizing Culinaria Modena and events become the main choice in marketing communication tactics.